2005
DOI: 10.1080/14622200500124875
|View full text |Cite
|
Sign up to set email alerts
|

The nicotine market: An attempt to estimate the nicotine intake from various sources and the total nicotine consumption in some countries

Abstract: Tobacco--particularly smoked products--has been associated with great harm and growing public disapproval and can be expected to suffer in the marketplace. This situation has created opportunities for other less harmful nicotine-containing products such as smokeless tobacco and nicotine replacement products, which are gaining public support. Little is known about the level of nicotine intake in our society. Tobacco sales are known, but how much nicotine is extracted and actually absorbed by users is largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…The results are also similar to a previous study in Sweden which has shown that approximately 54% of all nicotine comes from smoked sources, 45% from non-smoked tobacco and 1.3% from nicotine replacement products. For men, 63% of the nicotine consumed comes from non-smoked tobacco 32. This finding corresponds rather well with the observation in the present study that the prevalence of daily smoking is 14.9% but the prevalence of daily snus use is 19.5% among men.…”
Section: Discussionsupporting
confidence: 93%
“…The results are also similar to a previous study in Sweden which has shown that approximately 54% of all nicotine comes from smoked sources, 45% from non-smoked tobacco and 1.3% from nicotine replacement products. For men, 63% of the nicotine consumed comes from non-smoked tobacco 32. This finding corresponds rather well with the observation in the present study that the prevalence of daily smoking is 14.9% but the prevalence of daily snus use is 19.5% among men.…”
Section: Discussionsupporting
confidence: 93%
“…The possible cause of this association is obscure. Our finding that the use of snuff entails a decreased risk of hand eczema proposes the hypothesis that the effect of tobacco smoking is not caused by nicotine because the level of nicotine is higher when using snuff than when smoking [29].…”
Section: Discussionmentioning
confidence: 78%
“…Five male Japanese smokers provided information on the numbers of cigarettes smoked daily (mean, 31.0) [8]; using a value of 1.4 mg nicotine intake per cigarette [38], the estimated daily nicotine intake was 43.4 mg. This was one of the repetitive pooled samples for biomonitoring of plasma levels of nicotine and cotinine conducted after daily cigarette smoking in a population of 92 male Japanese smokers with a mean age of 37 years who had smoked an average of 23 cigarettes per day for 16 years [8].…”
Section: Resultsmentioning
confidence: 99%